2015
DOI: 10.4103/0973-6247.162695
|View full text |Cite
|
Sign up to set email alerts
|

Bombay blood group: Is prevalence decreasing with urbanization and the decreasing rate of consanguineous marriage

Abstract: Context:Bombay blood group although rare is found to be more prevalent in the Western and Southern states of India, believed to be associated with consanguineous marriage.Aims:To estimate the prevalence of the Bombay blood group (Oh) in the urban population of Puducherry. To find the effect of urbanization on consanguineous marriage and to establish whether consanguinity plays a part in the prevalence of Oh group. To compare Oh group prevalence with that of other neighboring states, where population is not pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Balgir RS, [7] 2005, Orissa (Kutia Kondh tribe) 254 2 0.787 3 Verma A et al, [11] 2011, Tirupti A.P. 26638 4021 7M+6F 0.048 4 Kavitha A et al, [13] 2016, Chennai 8903 338 (33%) 2 0.022 5 Rudrappan RB & Veeran K, [14] 2016, Chennai 11512 2 0.017 6 Geetha RL et al, [12] 2011, Bangalore 37117 15032 (40.5%) 2M+4F 0.016 7 Mahapatra et al, [15] Mallick et al, [16] 2015, Puducherry 35497 (Both donors & recipients) 14164 3 0.008 9 Talukder et al, [17] 2014 , Kolkata 56465 28934 Donors 27531 Patients 6 2 4 0.011 0.007 0.014 10 Singh A et al, [18] 2019, Lucknow (Consanguinity in 2 cases of Bombay) 177888 5M+1F 0.003…”
Section: Discussionmentioning
confidence: 99%
“…Balgir RS, [7] 2005, Orissa (Kutia Kondh tribe) 254 2 0.787 3 Verma A et al, [11] 2011, Tirupti A.P. 26638 4021 7M+6F 0.048 4 Kavitha A et al, [13] 2016, Chennai 8903 338 (33%) 2 0.022 5 Rudrappan RB & Veeran K, [14] 2016, Chennai 11512 2 0.017 6 Geetha RL et al, [12] 2011, Bangalore 37117 15032 (40.5%) 2M+4F 0.016 7 Mahapatra et al, [15] Mallick et al, [16] 2015, Puducherry 35497 (Both donors & recipients) 14164 3 0.008 9 Talukder et al, [17] 2014 , Kolkata 56465 28934 Donors 27531 Patients 6 2 4 0.011 0.007 0.014 10 Singh A et al, [18] 2019, Lucknow (Consanguinity in 2 cases of Bombay) 177888 5M+1F 0.003…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Bombay phenotype is 1:10,000 in India however it is much less prevalent in the Caucasians with an incidence of 1:250,000 [4]. A study amongst an urban population in Puducherry, India demonstrated that 0.008% population had Bombay blood group and it was strongly associated with consanguineous marriage (66.66%) [5]. This prompts for pre-marital blood phenotyping for all individuals and discouragement of marriage amongst individuals carrying the h allele.…”
Section: Discussionmentioning
confidence: 99%
“…Bombay blood type was known as the rarest in the world. The probability of finding a person with Bombay was one for every 250.000 worldwide ( 1 ). Bombay individuals was characterized by the absence of A, B and H antigens on red blood cells and associated with anti-H antibodies in plasma.…”
Section: Dear Editor-in-chiefmentioning
confidence: 99%